Hubungan antara Luas Panen Padi terhadap Emisi Metana di Indonesia: Analisis Data FAO dan BPS - salsa fajriya; Apip Supriadi; Asep Yusup Hanapia; Rivan Indra Maulana; Rohyatul Kirom; Rosie Suci Pebriani; Shafdiar Gustira (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2026)
Abstract: This study aims to analyze and describe the trend of Rice Harvest Area in Indonesia using data from the Central Bureau of Statistics (BPS) and the trend of methane (CH4) emissions from the rice agriculture sector based on data from the Food and Agriculture Organization of the United Nations (FAO) for the 2018–2022 period. The study also identifies the quantitative relationship between the Rice Harvest Area and the amount of methane gas emissions in Indonesia. The type of research used is descriptive quantitative, utilizing secondary data from BPS for the Harvest Area and from FAO for the Total Agricultural Methane Emissions. Methane emission calculations were performed using an emission factor-based approach from the IPCC 2006 Guidelines 4, with the assumption of a continuously flooded water regime (SFw = 1.0), and the analysis of the relationship between variables used the Pearson Correlation method. The results show that the trend of the rice harvest area and the annual methane emission trend exhibit a very similar pattern, generally declining from 2018 to 2021 before slightly increasing in 2022. Furthermore, the Pearson correlation analysis results show a value of r = 1.00, which indicates a very strong positive correlation between the Rice Harvest Area and the Annual Methane Emissions. This finding confirms that the increase in the rice harvest area directly contributes to the increase in total methane emissions released into the atmosphere because flooded rice fields create anaerobic conditions that are ideal for methane-producing microorganism. Keywords: Rice Harvest Area; Methane Emissions (CH4); Pearson Correlation; FAO; BPS. Abstrak: Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan tren Luas Panen padi di Indonesia menggunakan data Badan Pusat Statistik (BPS) serta tren emisi metana (CH4) dari sektor pertanian padi berdasarkan data Food and Agriculture Organization of the United Nations (FAO) periode 2018–2022. Penelitian ini juga mengidentifikasi hubungan kuantitatif antara Luas Panen padi dengan jumlah emisi gas metana di Indonesia. Jenis penelitian yang digunakan adalah kuantitatif deskriptif dengan menggunakan data sekunder dari BPS untuk Luas Panen dan FAO untuk Total Emisi Metana Pertanian. Perhitungan emisi metana dilakukan dengan pendekatan berbasis faktor emisi dari IPCC 2006 Guidelines, dengan asumsi rezim air tergenang terus-menerus (SFw = 1.0), dan analisis hubungan antar variabel menggunakan metode Korelasi Pearson. Hasil penelitian menunjukkan bahwa tren luas panen padi dan tren emisi metana tahunan memiliki pola yang sangat mirip, cenderung menurun dari tahun 2018 ke 2021 sebelum sedikit meningkat pada tahun 2022. Lebih lanjut, hasil analisis korelasi Pearson menunjukkan nilai r = 1.00, yang mengindikasikan adanya korelasi positif yang sangat kuat antara Luas Panen padi dan Emisi Metana Tahunan. Temuan ini menegaskan bahwa peningkatan luas panen padi secara langsung berkontribusi terhadap peningkatan total emisi metana yang dilepaskan ke atmosfer, karena lahan sawah yang tergenang menciptakan kondisi anaerob yang ideal bagi mikroorganisme penghasil metana.